Penggunaan Media Video Animasi untuk Meningkatkan Motivasi Belajar Sejarah pada Siswa SMA Isen Mulang Palangka Raya Kalimantan Tengah - Vivi Friskila Angela; Defri Triadi (STKIP PGRI SITUBONDO, 2022)
In this pandemic condition, a teacher must develop the application of learning competence methods so that students do not feel awkward in receiving subject matter, while on the other hand specifically in the context of history subjects, both in pandemic conditions or not, history teachers have difficulty in attracting or motivating students to feel interested in historical subjects, even though they have used learning methods that have been conceptualized carefully. Therefore, this pandemic condition should stimulate history teachers to create creative learning so that students have the motivation to learn history. This study aims to find out how the use of animated video media increases students' motivation to learn history at SMA Isen Mulang Palangka Raya, Central Kalimantan. This study uses a qualitative approach with a descriptive type, and the technical analysis of the data used in this study is to systematically compile the data obtained from interviews, field notes, and documentation, by organizing the data into categories, describing them into units, arranging into patterns, determine which ones are important and which ones will be studied, and make conclusions so that they are easier to understand.